Assessment of Thermal Pollution at Selected Stretch of Tigris River in Baghdad by Field Observations and Numerical Simulations (Journal of Engineering, 2022)
Although many technological improvements are occurring in power production worldwide, power plants in third world countries are still using old technologies that are causing thermal pollution to the water bodies. Power facilities that dump hot water into water bodies are damaging aquatic life. In the study, the impact of the Al Dora thermal power plant on a nearby stretch of Tigris River in Baghdad city was assessed by measuring the temperature of the disposed of hot water in various cross-sections of the selected stretch of Tigris River, including measuring the thermal mixing length. The measurements were conducted in winter, spring, and summer. For field measurements, it was found that the impact of recovery distances extended to 1500, 1810, and 2450 m in winter, spring, and summer seasons, respectively. Also, the impact of the thermal pollution was simulated using the CFD COMSOL model. When these values were compared with the predicted values, the measured values were found smaller than the predicted by using the heat equation for temperature recovery distances. Also, the simulation included the impact of reducing the velocity of the disposed of hot water on the temperature distribution and mixing length in the studied stretch of Tigris River. Simulation results show that when the velocity of the disposed of hot water was reduced from 1.6 to 0.5 m/s, the thermal mixing in the Tigris River improved. The estimation of dissolved oxygen concentrations was found to range from 6.9 to 10.7 mg/l, which is higher than the critical concentration of 5 mg/l, which is required for aquatic life.